Reforma al art. 267 del código orgánico integral penal, en cuanto a la sanción a las personas jurídicas por reincidencia en delitos contra la actividad hidrocarburífera, derivados de hidrocarburos, gas licuado de petroleo y biocombustibles - Quezada Orellana, Franklin Eduardo (2015)
The Constitution of the Republic of Ecuador, establishes in its Art.3 numerals 7 the primary duty of the State to defend the country's natural and cultural heritage and protecting the environment; and, to preserve the sustainable growth of the economy, and the balanced and equitable development for the collective benefit So the Constitution of the Republic, to guarantee the healthy and normal development of the citizens, protecting their environment and natural environment so much as cultural. In the same way in the same legal body in its Art.15, settles down, the Constitution of the Republic of Ecuador, article 15 provides that "the State will promote, in the public and private sectors, the use of environmentally clean technologies and non-polluting alternative energies and low impact. Energy sovereignty will not be achieved at the expense of food, or affect the right to water" Also the Constitution of the Republic of Ecuador, establishes in its article 313 that: "the State reserves the right to manage, regulate, control and manage the strategic sectors, in accordance with the principles of environmental sustainability, precaution, prevention and efficiency. Strategic sectors, of decision and exclusive control of the State, are those who by their 6 significance and magnitude have decisive influence economic, social, political or environmental, and must orient itself to the full development of the rights and the social interest. Are considered strategic sectors energy in all its forms, telecommunications, non-renewable natural resources, transportation and refining of hydrocarbons, biodiversity and genetic heritage, radio spectrum, the water, and others that determined by law" As a result, both subsidy derived from hydrocarbon liquid fuels, including gas liquefied petroleum, taken over by the State, has caused that unscrupulous people do abuse him, through the illicit trade in these fuels, derived from hydrocarbons, which has generated and generates serious prejudice to the State budget. In addition in recent years have systematically made fraudulent subtractions and tampering of hydrocarbon-derived liquid fuels, including liquefied petroleum gas, using different methods and forms; facts that have been appropriately reported to the Prosecutor's Office. It is worth mentioning that article 1 - A of the hydrocarbons law determines "in the activities of hydrocarbons, practical agreement or regulations that impede or distort free competition, by the private or public sector. Also practical agreement or actions seeking the deliberate shortages in the domestic market of hydrocarbons" The organic code criminal Integral in its Art.267 determines that "If criminal liability of a legal person by the actions typified in this section will be punished with a fine of five hundred to one thousand Basic unified worker wages in general" That is to say, the State guarantees and punishes the adulteration of the quality of the oil and gas derivatives, the suspension of the service, storage, transport, marketing or illegal distribution or bad spindle of derivatives of hydrocarbons and fuels; but the problem is that this article of the 2nd paragraph of chapter IV of title IV of the organic comprehensive criminal code and the special law of hydrocarbons alone establish the sanction to the recurrence of natural persons for the crimes against the hydrocarbon activity, derivatives of hydrocarbons, liquefied petroleum gas and biofuels; Therefore, urgent reform to the Integral Penal organic code, where is established as a sanction to the recurrence of this kind of crimes committed by legal persons, not only with the already established fine, but also with the recidivism by twice having a temporary closure of 15 days and a third time with the permanent closure is required